A Mechanistic Study of the Association Between Symbolic Approximate Arithmetic Performance and Basic Number Magnitude Processing Based on Task Difficulty - Wei, Wei; Deng, Wanying; Chen, Chen; He, Jie; Qin, Jike; Kovas, Yulia (Frontiers in Psychology, 2018)
Two types of number magnitude processing— semantic and spatial—are significantly correlated with children’s arithmetic performance. However, it remains unclear whether these abilities are independent predictors of symbolic approximate arithmetic. The current study addressed this question by assessing 86 kindergartners (mean age of 5 years 7 months) on semantic number processing (number comparison task), spatial number processing (number line estimation task) and symbolic approximate arithmetic with different levels of difficulty. The results showed that performance on both tasks of number magnitude processing was significantly correlated with symbolic approximate arithmetic, but the strength of these correlations was moderated by the difficulty level of arithmetic. The simple symbolic approximate arithmetic task was equally related to both tasks. In contrast, for more difficult symbolic approximate arithmetic, the contribution of number comparison was smaller than that of the number line estimation. These results indicate that the strength of contribution of the different types of numerical processing depends on the symbolic approximate arithmetic’s difficulty.